Human Salivary Histatin-1 Is More Efficacious in Promoting Acute Skin Wound Healing Than Acellular Dermal Matrix Paste - Lei, Xiaoxuan; Cheng, Liuhanghang; Lin, Haiyan; Pang, Mengru; Yao, Zexin; Chen, Caihong; Forouzanfar, Tymour; Bikker, Floris J.; Wu, Gang; Cheng, Biao (Frontiers in Bioengineering and Biotechnology, 2020)
A rapid wound healing is beneficial for not only recovering aesthetics but also reducing pain, complications and healthcare burdens. Acellular dermal matrix (ADM) paste has been used to repair burn wounds and is shown to promote angiogenesis as well as fibroblast attachment and migration. However, its efficacy still needs to be significantly improved to meet clinical demands. To approach this problem, we adopted a human salivary peptide — Histatin 1 (Hst1). Hst1 was chosen because of its potency to promote the adhesion, spreading, migration, metabolic activity and cell-cell junction of major skin cells. In this study, we hypothesized that ADM paste and Hst1 additively or synergistically promoted the healing of surgically-created acute skin wounds in mice since ADM paste may act as a slow release system for Hst1. Our results showed that the healing efficacy of 10 μM topically administrated Hst1 was significantly higher compared to the control (no Hst1, no ADM) from day 3 to day 10 post-surgery. In contrast, ADM alone failed in our system at all time points. Also, the combination of ADM paste and Hst1 did not show any synergistic or additive effect in wound healing rate. Histological analysis showed that 10 μM Hst1 was associated with maximal thickness of newly formed epidermal layer on day 7 as well as the largest collagen area on day 14. In addition, immunohistochemical staining showed that the number of CD31-positive blood vessels in the group of 10 μM Hst1 was 2.3 times compared to the control. The vascular endothelial growth factor (VEGF) expression in the groups of 10 μM Hst1 group and ADM+10 μM Hst1 group was significantly higher compared with the control group. Furthermore, 10 μM Hst1 group was associated with significantly lower levels of CD68-positive macrophage number, interleukin-1β (IL-1β) expression and C-reactive protein (CRP) expression than those of the other groups (control, ADM alone and ADM+10 μM Hst1). The co-administration of Hst1 and ADM paste did not yield more beneficial effects than Hst1 alone. In conclusion, the topical administrated of 10 μM Hst1 could be a promising alternative dressing in managing acute wound healing.